Oleksiy Chekal: Letters and Meanings - Rybalko, Svitlana; Cheng, Zhou (HUDPROM: The Ukrainian Art and Design Journal, 2024)
The article explores the creative legacy of renowned Ukrainian calligrapher and designer Oleksiy Chekal, a graduate of the Kharkiv State Academy of Design and Arts. The proposed research work systematizes and analyzes the materials related to the artist’s creative practice, including his works, masterclasses, interviews, and written texts. It identifies the most representative works that showcase his artistic explorations, experiments, and diverse creative challenges. The article traces the key stages in the formation of Chekal’s creative interests and artistic background, as well as the Ukrainian and international creative influences that have shaped the artist’s work. Special attention is paid to the creative and pedagogical environment of Kharkiv and Kharkiv State Academy of Design and Arts, where Oleksiy Chekal got his education and continues to collaborate with teachers of KSADA. The study employs a range of research methods, including general scientific approaches (systematization, typology, biographical, and comparative analysis), art analysis techniques (formal, figurative-stylistic, semantic, and hermeneutical types of analysis), and field research methods (empirical observation, interviews, video and photographic documentation). The novelty of this research lies in the fact that it is the first systematic study to analyze and introduce Chekal’s creative achievments into academic discourse. It outlines the trajectory of his artistic development, examines the stylistic features of his calligraphic compositions within both Ukrainian and global contexts, and highlights his contributions to pedagogy, exhibitions, and social initiatives. The article underscores the significance of Chekal’s work in preserving and advancing the Ukrainian calligraphic tradition.